A legal study on the offence of exceeding speed limits and its punishment as provided under Road Transport Act 1987 and Land Public Transport Act 2010 / Mohd Tajaruddin Seman, Nurul Ashikin Shaarani and Nurzulyana Norzali - Seman, Mohd Tajaruddin; Shaarani, Nurul Ashikin; Norzali, Nurzulyana (2011)
Due to an increasing number of road traffic offences in Malaysia which cause lots of accident occurred, the offenders are said to not have been punished. A legal study on the offence of exceeding speed limits and its punishment as provided under Road Transport Act 1987 and Land Public Transport Act 2010 will be conducted to scrutinize the offence and its punishment towards the road traffic offenders. Therefore the aims of this study are to analyze the punishment impose in deterring road traffic offenders under both Acts and to suggest an alternative punishment in reducing the number of road traffic offenders. The target group of the interviews would be the higher authorities that deal directly with the problem namely Traffic Branch of The Royal Malaysian Police, and Jabatan Pengangkutan Jalan (JPJ). It is aimed to provide better understanding regarding the offence of exceeding speed limits and punishment imposed to the traffic offender, whether the existence punishment under both Acts is severe and sufficient enough in order to deter the offence or merely because there is a lack of enforcement on the part of the enforcement agencies. Significantly, this research study is helped to be one of the platforms to enhance the existing law in Malaysia so that the law will deter the crime effectively and this research will be a stepping stone to the legislative body in playing their roles to impose an effective punishment towards the traffic offenders in order to deter the crimes successfully.